A mem-element Wien-Bridge circuit with amplitude modulation and three kinds of offset boosting. (December 2022) - Du, Chuanhong; Liu, Licai; Zhang, Zhengping; Yu, Shixing
Abstract: In the field of information processing, peripherals are often required to modulate the signal in terms of amplitude and position. At present, amplitude and offset boosting control of chaotic signals are mainly achieved by introducing additional constants or functions, and few systems rely on their parameters. In this work, a Wien-Bridge circuit is designed based on a voltage-controlled memristor. In addition to implementing the boosting control by introducing additional constants, the system exhibits both linear and nonlinear offset boosting behavior and amplitude control by changing the system's parameters. This facilitates the reduction of the number of external devices for signal modulation. Besides, the system also presents coexisting symmetric attractors and bistability. These dynamic characteristics are investigated using Lyapunov exponents, bifurcation diagram, attractor projection, frequency spectra, attraction basin, and chaotic characteristic diagram. Finally, the system is implemented using DSP, which provides the basis for the application of chaotic modulation. Highlights: Three kinds of offset boosting behaviors are reported for the first time. The system can achieve linear offset boosting under seven different attractors. Changing the system parameters also allows for both amplitude and spectral modulation. Having the symmetric coexisting attractors, bistability, and a wide range of chaos. The DSP implementation provides the basis for the application of chaotic modulation.